A Rare Case of Massive Hematocolpos Due to Imperforate Hymen - Meher-un-Nisa, Andleeb Arshad, Saira Iqbal, Komal Mannan, Shahab Saad Ali, Bushra Saeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Imperforate hymen is a very rare anomaly of female reproductive system due to failure of complete canalization of endoderm of urogenital sinus thus obstructing the vaginal opening1, The condition is often diagnosed late due to its low incidence, nonspecific presentation & insufficient physical examination. The teenage girls with imperforate hymen generally present with cyclical lower abdominal pain without the menstruation being established, urinary retention or constipation and sometimes as lower abdominal mass.Diagnosis is clinical and confirmed by ultrasound. It is treated surgically.